Híbridos de milho submetidos a diferentes temperaturas de secagem em dietas suplementadas com ou sem enzimas para frangos de corte - Giacobbo, Franciele Clenice Navarini (2020)
This work aimed to evaluate the effects of three different maize hybrids, two grain drying temperatures of 80 and 110 ° C and the effect of the inclusion on top of exogenous enzymes in different diets for broilers. Initially, it was determined the chemical composition of the grain, content of non-starch polysaccharides (PNA's), retrograde starch, analysis of the starch morphology and the values of apparent metabolizable energy (AME), AME corrected for the nitrogen balance (AMEn) and the coefficients of nitrogen apparent and corrected metabolizable (AMC and AMCn). The energy values were determined by the traditional method of total excreta collection, using broilers from 11 to 21 days of age, allocated in a completely randomized design, in a factorial scheme (three corn hybrids and two drying temperatures - 80 and 110 ° C), totaling six treatments, with seven replications and four birds per experimental unit. The results were subjected to analysis of variance and the individual effects and the interaction between the factors (hybrid and temperature) were analyzed; when significant, the interactions were unfolded. In general, the dried grains at 110 ° C showed a higher content of amylose and resistant starch, a higher content of nitrogen bound to fiber, with a reduction in the content of soluble PNA's in relation to the totals and a reduction in the size of the starch grain. There was an interaction (P <0.05) between the factors evaluated for the AME and AMEn values. The energy values within each drying temperature have not shown interference from the hybrids (P> 0.05). However, when the drying temperatures within each hybrid were evaluated, the AME and AMEn values of 3,373 and 3,300 kcal kg-1, respectively, obtained for hybrid 1 dried at 110 ° C, reduced by 73 and 69 Kcal. For the isolated factors, regardless of the drying temperature, hybrid 3 presented higher AMC and AMCn, values of 83.10 and 81.98%, respectively. The drying temperature provided variation in the chemical composition of the corn grain. The grain exposed to drying at 110 ° C showed an increase in the levels of amylose and resistant starch, a reduction in the ratio of soluble PNAs in relation to the total and an increase in nitrogen bound to fiber. However, in general, these structural changes were not able to provide differences in energy values. The second experiment aimed to determine the influence of different corn hybrids and drying temperature, as well as the effect of the inclusion of exogenous enzymes on the ileal digestibility of nutrients, on performance, carcass yield, intestinal morphometry and cecal microbiota of broilers. For this purpose, 2,160 male day-old broiler chicks were used, distributed in a completely randomized design, in a 3 x 2 x 2 factorial scheme (three corn hybrids, two drying temperatures - 80 and 110 ° C, with and without addition on top of enzymatic blend (15000 PROT.kg-1 protease, 80 KNU.kg-1 amylase and 100 FXU.kg-1 xylanase), totaling 12 treatments, with nine replicates and 20 birds per experimental unit. contained 1000 FYU.kg-1 of phytase. For the performance and digestibility parameters, it was observed that, in general, there was punctual interference of the hybrid factors and drying temperature of corn. The addition on top of an enzymatic blend composed of xylanase, amylase and protease, provided better performance, intestinal morphometric parameters, greater presence of the genus of bacteria Lactobacillus, Ruminococcus and Anaeroplasma, in the initial phase of life (one to 21 days) in broilers and better nutrient digestibility at 42 days of age. However, the addition of the enzymatic blend in the compound diet with grains exposed to drying temperature of 110 ° C has not been able to express differences in the parameters of performance and digestibility.